2014
DOI: 10.1007/s12035-014-8835-1
|View full text |Cite
|
Sign up to set email alerts
|

1,25-dyhydroxyvitamin D3 Attenuates l-DOPA-Induced Neurotoxicity in Neural Stem Cells

Abstract: The neurotoxicity of levodopa (L-DOPA) on neural stem cells (NSCs) and treatment strategies to protect NSCs from this neurotoxicity remain to be elucidated. Recently, an active form of vitamin D3 has been reported to display neuroprotective properties. Therefore, we investigated the protective effect of 1,25-dyhydroxyvitamin D3 (calcitriol) on L-DOPA-induced NSC injury. We measured cell viability via the cell counting kit-8 (CCK-8) and lactate dehydrogenase (LDH) assays and Annexin V/PI staining followed by fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…It was reported that calcitriol can significantly decrease apoptosis in levodopa-induced neural stem cell injury. 9 In addition, similar therapeutic effects were confirmed in an in vitro model of Parkinson's disease. 10 Therefore, calcitriol treatment reduces Effects of calcitriol on SCI K-l Zhou et al the level of cell apoptosis in many diseases.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…It was reported that calcitriol can significantly decrease apoptosis in levodopa-induced neural stem cell injury. 9 In addition, similar therapeutic effects were confirmed in an in vitro model of Parkinson's disease. 10 Therefore, calcitriol treatment reduces Effects of calcitriol on SCI K-l Zhou et al the level of cell apoptosis in many diseases.…”
Section: Discussionmentioning
confidence: 71%
“…8 Calcitriol attenuates levodopa-induced neurotoxicity in neural stem cells by significantly reducing apoptosis. 9 In addition, calcitriol has been reported to upregulate the level of cellular autophagy. 10 However, its relevance to promotion of functional recovery after SCI in rats has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…7 Moreover, it seems that the active form of vitamin D could activate p38 mitogen-activated protein kinase and phosphatidylinositol kinase 24 , which induces oxidative stress and consequently a structural disintegration and stiffening of the arterial wall. 25 Altogether these findings suggest that low vitamin D levels could play a role in reducing compliance in arteries making difficult the adaptation during standing up. Second, some research have shown that hypovitaminosis D could be associated with a dysfunction of the baroreflex neural arc (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, many studies of PD models have demonstrated roles for vitamin D in neuronal cell differentiation and neuroprotection via various mechanisms [17,18,19,20,21]. Therefore, vitamin D may be neuroprotective against PD-related degenerative processes in the dorsal motor vagal system and enteric nervous system, indicating that vitamin D plays an important role in gastric dysmotility in PD.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have demonstrated an additional role for vitamin D in neuroprotection through various mechanisms, including antioxidation, neuronal calcium regulation, immunomodulation, enhanced nerve conduction, detoxification and autophagy [16,17,18,19,20,21]. Furthermore, vitamin D has recently been suggested to be involved in the pathogenesis and progression of PD [22], and recently, we reported that vitamin D levels were associated with orthostatic hypotension in PD patients [23].…”
Section: Introductionmentioning
confidence: 99%